Pengaruh Struktur Keuangan Terhadap Profitabilitas Perusahaan Pada PT Darma Henwa Tbk - Refli Sudrajat; Nurmala Nurmala; Bambang Purwanto (Jurnal Riset Akuntansi dan Manajemen Malahayati, 2013)
Financial structure is a combination of all sources of financing that the company obtainedshort-term debt , long-term debt and common stock and preferred stock ( equity ) , the use of sourcesof financing can be used as a measure of the increase in profits in a company , so the effect of debt andcapital can serve as a main point company to finance company in terms of maximizing the value of thecompany . This research was conducted at PT Darma Henwa Tbk period 2007-2010 by using multiplelinear regression analysis .Based on the results obtained by multiple linear regression analysis equationY = -7.998 - 0.025 0.242 X1 + X2 . Test simultaneously obtained significant F value = 0.001 < α 0.05,which means that the financial structure is represented by the variable Debt to Equity Ratio ( DER )and Debt to Assets Ratio ( DAR ) simultaneously significant effect on the profitability of the companyat PT Darma Henwa Tbk , as well as the variable DAR , which became the most dominant variablesknown to affect the profitability of seeing the value that is equal to 1.606 Standardized Coefficients .The influence of financial structure is represented by the variable DER and Debt to Assets Ratio tocompany profitability is equal to 59.5 %.Keywords: DER, DAR